2015
DOI: 10.1007/s11571-015-9363-z
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic preference recognition of 3D shapes using EEG

Abstract: Recognition and identification of aesthetic preference is indispensable in industrial design. Humans tend to pursue products with aesthetic values and make buying decisions based on their aesthetic preferences. The existence of neuromarketing is to understand consumer responses toward marketing stimuli by using imaging techniques and recognition of physiological parameters. Numerous studies have been done to understand the relationship between human, art and aesthetics. In this paper, we present a novel prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 43 publications
(43 reference statements)
0
51
0
Order By: Relevance
“…Although the answer to what are the most emotion-relevant EEG features is still under investigation, power features from different frequency bands are still the most popular in the context of emotion recognition. Studies [26,197,218] have shown that power spectral density (PSD) extracted from EEG signals performs well on distinguishing affective states.…”
Section: Eeg Correlates Of Emotion (Signals)mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the answer to what are the most emotion-relevant EEG features is still under investigation, power features from different frequency bands are still the most popular in the context of emotion recognition. Studies [26,197,218] have shown that power spectral density (PSD) extracted from EEG signals performs well on distinguishing affective states.…”
Section: Eeg Correlates Of Emotion (Signals)mentioning
confidence: 99%
“…[102,123,218,280] Education These articles tracked students' engagement and learning. [38,281] Assistance These articles explored how assistive technologies or learning resources were provided to individuals.…”
Section: Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…We have conducted a number of prior investigations into the use of electroencephalography (EEG) as a method for passively monitoring the brainwaves of users as they are exposed to 3D visual stimuli as well as immersive stimuli and then using different machine learning algorithms to predict their preferences among the various visual stimuli [1], [2]. In the first part our study, we focus on human preference classification.…”
Section: Introductionmentioning
confidence: 99%
“…In our early work with a small set of five test subjects, good classification rates of up to 80% were attained using simple knearest neighbor (kNN) classifiers [1]. However, when the number of test subjects was increased to 16, the noise arising from inter-subject variability became a substantial factor which made the classification process significantly more challenging [2].…”
Section: Introductionmentioning
confidence: 99%